The molecular control and biological implications of autolysis in enterococcus faecalis biofilm development - Chittezham Thomas, Vinai (Kansas State University, 2009)
The enterococci are gaining much notoriety as common nosocomial pathogens. One aspect of their pathogenesis, especially characteristic to infectious endocarditis and urinary tract infections, involves their ability to transition from the sessile state of existence to surface adherent structured communities called biofilms. Existence as biofilms, affords enterococci protection against a number of growth limiting challenges including antibiotic therapy and host immunity. In the current study a mechanistic role for two Fsr quorum-regulated extracellular proteases- gelatinase (GelE) and its cotranscribed serine protease (SprE), were explored in biofilm development of E. faecalis V583. Confocal imaging of biofilms suggested that GelE[superscript]– mutants were significantly reduced in biofilm biomass compared to V583, whereas the absence of SprE appeared to accelerate the progression of biofilm development. Culture supernatant and biofilm analysis confirmed that decreased biofilms observed in GelE[superscript]– mutants resulted from their inability to undergo autolysis and release extracellular DNA (eDNA) in planktonic and biofilm cultures, whereas SprE[superscript]– mutants produced significantly more eDNA as components of the biofilm matrix. The governing principle behind GelE mediated autolysis and eDNA release in E. faecalis V583 was demonstrated to be fratricide. GFP reporter assays of V583 populations confirmed that GBAP (gelatinase biosynthesis-activating pheromone encoded by fsrD) quorum non-responders (GelE[superscript]–SprE[superscript]–) were a minority subpopulation of prey cells susceptible to the targeted fratricidal action of the quorum responsive predatorial majority (GelE[superscript]+SprE[superscript]+). The killing action is dependent on GelE, and the GelE producer population is protected from self-destruction by the co-production of SprE as an immunity protein. Targeted gene inactivation and protein interaction studies demonstrate that extracellular proteases execute their characteristic effects following downstream interactions with the primary autolysin, AtlA. Finally, comparison of virulence effects of isogenic extracellular protease mutants (∆gelE, ∆sprE and ∆gelEsprE) relative to parental strain (V583) in a rabbit model of enterococcal endocarditis confirmed a critical role for GelE in the infection process. In conclusion, the data presented in this thesis are consistent with significant roles for GelE and SprE in biofilm mediated pathogenesis of enterococcal infections.
Keywords: Enterococcus faecalis; autolysis; fratricide; biofilm; gelatinase; serine protease; Biology, Microbiology (0410); Biology, Molecular (0307)